Prevalence of Pangasius Fish Disease in Nepal (Tribhuvan University Journal of Microbiology, 2023)
Objectives: This study was conducted to identify bacterial pathogens in both symptomatic and asymptomatic enteric septicemic infection of Pangasiaus hypophthalmus and evaluate their susceptibility to antibiotics.Methods: The totals of 120 kidney and liver swab samples of fish were collected from different places of Nepal. The samples were processed to identify the causative agent using pure culture of bacteria through streak plate techniques and different biochemical tests. To assess the susceptibility of the isolated bacteria to antibiotics Ciprofloxacin, Tetracycline, Doxycycline, Gentamycin, Ampicillin/ sulbactam, and Tobramycin were used.Results: The estimated prevalence of pathogenic bacteria is 27 per 10000 populations. Three pathogenic bacteria i.e. Edwardsiella ictaluri 57.7% (56/97), Aeromonas hydrophila 24.7% (24/97), and Pseudomonas fluorescence 17.5% (17/97) were identified in the studied asymptomatic and symptomatic Pangas fish disease. E. ictaluri was major isolates which was causative agent for the disease, enteric septicemia of catfish. Among the total bacterial isolates 100% bacterial isolates were sensitive to Ciprofloxacin and 84% to Gentamycin. Whereas 100% were resistance to Ampicillin and 84% to Tetracycline. And Tobramycin (60.8%) and Doxycycline (64.9%) showed intermediate result.Conclusion: Ciprofloxacin and Gentamycin could be administered to control enteric septicemia of catfish in Pangas. This study provides information to strategies to reduce economic losses to farmer and reduce possible health hazards.